2016
DOI: 10.1002/2015pa002848
|View full text |Cite
|
Sign up to set email alerts
|

Ring Index: A new strategy to evaluate the integrity of TEX86 paleothermometry

Abstract: The TEX 86 (tetraether index of 86 carbon atoms) sea surface temperature proxy has been increasingly applied in the reconstruction of Mesozoic and Cenozoic ocean temperatures. However, the archaeal lipids that compose TEX 86 indices, glycerol dialkyl glycerol tetraethers (GDGTs), can derive from water column production, terrestrial sources, and/or within sediments. TEX 86 -sea surface temperature estimates can also be influenced by non-temperature factors, such as growth phase and nutrient levels. Here we show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
206
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(212 citation statements)
references
References 71 publications
(154 reference statements)
5
206
1
Order By: Relevance
“…Regression analysis between TEX 86 and RI on the remaining 103 SPM data points showed that by sequentially removing nine outliers, defined as the RI values that exceed the 95% prediction band, RI and TEX 86 become highly correlated when fitted with a quadratic regression (Figure a). The quadratic regression between RI and TEX 86 in surface water is clearly different from the one relating sedimentary RI and TEX 86 in the global data set (Figure a) [ Zhang et al ., ], although both are similar in shape. This implies that the thermal response of isoGDGTs in surface water archaea is likely quantitatively different from global sedimentary isoGDGTs.…”
Section: Discussionmentioning
confidence: 99%
“…Regression analysis between TEX 86 and RI on the remaining 103 SPM data points showed that by sequentially removing nine outliers, defined as the RI values that exceed the 95% prediction band, RI and TEX 86 become highly correlated when fitted with a quadratic regression (Figure a). The quadratic regression between RI and TEX 86 in surface water is clearly different from the one relating sedimentary RI and TEX 86 in the global data set (Figure a) [ Zhang et al ., ], although both are similar in shape. This implies that the thermal response of isoGDGTs in surface water archaea is likely quantitatively different from global sedimentary isoGDGTs.…”
Section: Discussionmentioning
confidence: 99%
“…As an alternative to the relatively poor preservation of the foraminifera and issues with the calibration of organic-based proxies (1,5,17), this study exploits the coccoliths as a source of paleoclimatic information. Coccolithophores, single-celled phytoplankton algae, are a key component of the carbon cycle and the ocean biological pump, and their calcite biominerals, the coccoliths, are a major component of pelagic sediments.…”
mentioning
confidence: 99%
“…So far, only a handful of sites serve as a reference for climate history at low latitudes during the Eocene and the Eocene−Oligocene Transition (EOT): the nearshore Tanzania in the Indian Ocean [Tanzania Drilling Project (TDP)] (1,2) and open ocean sites in the equatorial Atlantic [Ocean Drilling Program sites ODP 925 and 929] (3)(4)(5). These records exhibit rather conflicting proxy data for the TDP and overall long-term cooling for the Atlantic sites 925 and 929.…”
mentioning
confidence: 99%
“…No samples had GDGT-2/crenarchaeol ratios > 0.4, indicating no GDGT input from methanotrophs (Weijers et al, 2011). As a final 285 exercise, the Ring Index (|ΔRI|) has been calculated for our dataset to identify all other non-temperature related influences on TEX 86 (Zhang et al, 2016). Using |ΔRI|>0.6 as a cutoff, two more samples were discarded.…”
mentioning
confidence: 99%
“…We have applied this index on samples analyzed by UHPLC/MS to see if TEX 86 values are reliable despite high BIT index values. In addition, we calculated the Methane Index (MI) (Zhang et al, 2011), GDGT-0/crenarchaeol (Blaga et al, 2009;Sinninghe Damste et al, 2009), GDGT-2/crenarchaeol ratios (Weijers et al, 2011), and Ring Index (Zhang et al, 2016) to check for input of methanogenic or methanotrophic 205 archaea, or any other non-temperature related biases to TEX 86 .…”
mentioning
confidence: 99%